Epistemerastes. The Platonic Philosopher in the Timaeus between True Opinion and Science - Casella, Federico (Revista Archai, 2021)
The aim of this paper is to analyse the ways in which the nature of true philosophers is described in Plato’s Timaeus. Byexamining the distinction between two kinds of opinion – one (produced by sensation) absolutely false, the other (developed through one of the soul’s rational faculties) reliably true – I will try to show that Plato coined a new term to denote both true philosophers and the characteristics of their knowledge. From being a ‘love of wisdom’, true philosophy came to be defined as a ‘passion for science’. Finally, I will try to illustrate the protreptic intent underlying this choice of words and how it concerns the main critical target of the Timaeus, the so-called Presocratics.